An unusual cause of peritonitis in a deployed environment. Issue 1 (19th November 2013) - Proffitt, Adrian; Faulconer, R; Kreishman, P; Graybill, S; Craig, D
Abstract : Acute abdominal pain is a common presenting complaint to both primary and secondary care, and is a frequent cause of hospital admission among deployed personnel. Identification of generalised peritonism on abdominal examination is a classical indicator of intra-abdominal pathology that may warrant exploratory laparotomy. Negative findings at laparotomy should serve as a diagnostic prompt to consider other non-surgical mimics of an acute abdomen.